Image analysis, classification and change detection in remote sensing: with algorithms for ENVI/IDL and Python - Canty, Morton John (CRC Press, 2014)
"The book introduces advanced undergraduates and graduates to techniques used in the processing of remote sensing digital imagery. It is intended for people who are working with remote sensing data in image analysis and GIS environments. The material is self-contained and illustrated with many programming examples in IDL, a computer language which supports the professional graphical user interface ENVI, one of the leading environments for remote sensing imagery analysis. The new edition includes Python-coded versions of the main image analysis algorithms discussed in the text, making it accessible to students and teachers without expensive ENVI/IDL licenses. "--